Prevalence and management of rubella susceptibility in healthcare workers in Italy: A systematic review and meta-analysis. (December 2022) - Bianchi, Francesco Paolo; Stefanizzi, Pasquale; Diella, Giusy; Martinelli, Andrea; Di Lorenzo, Antonio; Gallone, Maria Serena; Tafuri, Silvio
Abstract: Introduction: In the pre-vaccination era, all adults acquired immunity status due to natural infections during childhood and adolescence, whereas universal mass vaccination has changed the seroepidemiology of rubella among adults, showing lack of immunity in some subgroups. National and international guidelines recommend evaluating all healthcare workers (HCWs) for their immune status to rubella and possibly vaccinating those who are seronegative. We conducted a systematic review and meta-analysis to estimate the susceptibility rate to rubella among HCWs in Italy and to explore possible options for the management of those found to be susceptible. Methods: Eight studies were included in the meta-analysis, selected from scientific papers available in the MEDLINE/PubMed and Google Scholar (till page 10) databases between January 1, 2015 and November 30, 2021. The following terms were used for the search strategy: (sero* OR seroprevalence OR prevalence OR susceptibilit* OR immunit* OR immunogenict*) AND (healthcare worker* OR health personnel OR physician* OR nurse OR student*) AND (rubella OR german measles OR TORCH) AND (Italy) Results: The prevalence of rubella-susceptible HCWs was 9.0 % (95 %CI: 6.4–12.1 %). In a comparison of female vs. male serosusceptible HCWs, the RR was 0.67 (95 %CI = 0.51–0.88). Occupational medicine examinations for rubella screening with possible subsequent vaccination of seronegatives and exclusion of susceptible HCWs from high-risk settings were common management strategies. Conclusions: HCWs susceptible to rubella are an important epidemiological concern in Italy, and efforts to identify and actively offer the vaccine to this population should be increased.